2019
DOI: 10.1109/access.2019.2906506
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Selection Approach for Quality Control Mechanisms in Crowdsourcing

Abstract: Crowdsourcing has emerged as a new model for leveraging human knowledge and intelligence toward accomplishing tasks that are difficult to fulfill effectively with machines alone. However, owing to its open nature, quality control is a big challenge. Current crowdsourcing systems use one or two standard mechanisms for evaluation and quality control of a task, regardless of its type. In this paper, we propose a dynamic approach that exploits task-quality ontology to select the most suitable quality control mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…However, an ontology would need to be part of a framework that supports constant change while being used (Gil et al, 2017). Crowdsourcing has evolved as a new approach for leveraging human knowledge and intelligence to complete activities that are difficult for computers to complete efficiently (Alabduljabbar and Al-Dossari, 2019). Therefore, for the past few years, crowdsourcing has been used in the creation and development of ontologies (Gil et al, 2017;Khider et al, 2019;Waagmeester et al, 2020).…”
Section: Ontology Design Methodologiesmentioning
confidence: 99%
“…However, an ontology would need to be part of a framework that supports constant change while being used (Gil et al, 2017). Crowdsourcing has evolved as a new approach for leveraging human knowledge and intelligence to complete activities that are difficult for computers to complete efficiently (Alabduljabbar and Al-Dossari, 2019). Therefore, for the past few years, crowdsourcing has been used in the creation and development of ontologies (Gil et al, 2017;Khider et al, 2019;Waagmeester et al, 2020).…”
Section: Ontology Design Methodologiesmentioning
confidence: 99%
“…Hamrouni et al [6] proposed a photo-based MCS architecture that monitors the quality of the photos submitted by reporters to cover ongoing events. Alabduljabbar et al [7] studied a dynamic approach that exploits task-quality ontology to select the most suitable quality control mechanism for a given task based on its type. Ben Said et al [16] proposed an algorithm to determine the best public transport journey plan offering based on the quality of service of available WiFi mobile crowdsourced WiFi coverage along the journey.…”
Section: Related Workmentioning
confidence: 99%
“…The quality of the returned result, which is deduced from each worker's partial result, depends heavily on the characteristics of the recruited workers. To this end, most of the MCS research focused on hiring professional workers for each task such that they can complete the tasks' successfully and provide desired results [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Fabio et al evaluated 76 crowdsourcing projects found in 72 articles in [33], which helped researchers and crowdsourcers to understand the state-of-the-art of crowdsourcing and evaluated the quality management in crowdsourcing projects preliminary. In [34], Reham et al proposed a dynamic approach for selecting the best quality control mechanism for a task rather than selecting a special one for all types of tasks. Oleson et al present an inexpensive and scalable automated quality assurance process in [35], which relies on programmatic gold creation to provide targeted training feedback to workers and to prevent common scamming scenarios.…”
Section: Framework For Cap Problemsmentioning
confidence: 99%